Socio-demographic disparities in liver cancer mortality in China: a national analysis from 2015 to 2021 - Jing, Heya; Xu, Xiaofeng (Frontiers in Oncology, 2026)
IntroductionLiver cancer remains a leading cause of cancer-related mortality in China. Analyses based solely on crude mortality rates may obscure temporal trends and inequalities in the context of rapid population aging. This study examined recent trends and socio-demographic disparities in liver cancer mortality in China using age-standardized analyses.MethodsWe conducted a population-based analysis using data from the China National Mortality Surveillance System covering all 31 provincial-level regions of mainland China from 2015 to 2021. Liver cancer deaths were identified using ICD-10 code C22. Mortality rates were calculated for adults aged ≥20 years. Age-standardized mortality rates (ASMRs) were estimated by direct standardization to the 2010 China standard population. Temporal trends were assessed using joinpoint regression to estimate annual percent change (APC) and average annual percent change (AAPC). Disparities by sex, urban–rural residence, and geographic region were quantified using rate differences (RD), rate ratios (RR), and an index of disparity. Decomposition analysis was applied to assess the contributions of population aging and changes in age-specific mortality rates to crude mortality trends.ResultsBetween 2015 and 2021, a total of approximately 470,000 liver cancer deaths were recorded. The crude mortality rate changed modestly, whereas the ASMR declined steadily from 30.16 per 100,000 in 2015 to 23.60 per 100,000 in 2021. Joinpoint regression showed a significant overall decline in ASMRs (AAPC −4.0%, 95% CI −5.2% to −2.8%), with no statistically significant joinpoints detected. Throughout the study period, males had substantially higher ASMRs than females (2021: 36.9 vs. 13.8 per 100,000; RR = 2.67). Rural areas consistently exhibited higher ASMRs than urban areas, with the rural–urban RD widening from 6.4 per 100,000 in 2015 to 8.5 per 100,000 in 2021. Regionally, ASMRs declined more rapidly in Eastern China (29.7 to 22.6 per 100,000) than in Central (31.1 to 29.8 per 100,000) and Western China (30.4 to 28.7 per 100,000), resulting in increasing regional disparity. Age-specific mortality increased sharply with advancing age. Decomposition analysis indicated that population aging increased crude mortality, partially offset by reductions in age-specific mortality rates.ConclusionsLiver cancer mortality in China declined from 2015 to 2021 after age standardization; however, substantial and widening disparities by sex, urban–rural residence, age, and region persist. These findings highlight the importance of age-standardized and equity-focused approaches to liver cancer prevention and control.